A surface-modified porous iron-based scaffold and its preparation method and application

Through the electrochemical de -alloy technology, the nano -topological structure is constructed on the surface of the polyiteric iron bracket, which solves the problem of too slow degradation rate of iron -based implantation, and achieves high -efficiency degradation and bone regeneration rates of the bracket.

CN116407687BActive Publication Date: 2025-01-28SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111664394.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2025-01-28
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

The degradation rate of iron-based implants in the human body is too slow, resulting in a mismatch between the formation rate of new bones, affecting the healing speed and repair of bone defects.

Method used

Through the electrochemical de -alloy technology, the nano -topological structure is constructed on the surface of the porous iron -based bracket to increase its contact area with the solution, thereby increasing its degradation rate.

Benefits of technology

It significantly improves the degradation rate of iron -based brackets, matches it with the bone regeneration rate, enhances the bracket to promote bone ability, and meets the dynamic adaptation of the mechanical properties and degradation rates during service in the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116407687B_ABST
    Figure CN116407687B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of biomedical materials, and in particular to a surface-modified porous iron-based scaffold and a preparation method and application thereof. The present invention performs surface modification on an existing porous Fe-based scaffold, regulates the surface morphology and structure of the scaffold, and makes the degradation rate faster without destroying its mechanical properties. Experimental verification shows that the scaffold has good biocompatibility and can promote the proliferation and differentiation of osteoblasts on its surface, thereby achieving a perfect match between the degradation rate of the scaffold in vivo and the bone regeneration rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical materials, and in particular to a surface-modified porous iron-based scaffold and a preparation method and application thereof. Background Art

[0002] Bone defects caused by diseases, trauma, traffic accidents, etc. have become common clinical diseases. Since most bone defect repairs require the assistance of implants, and autologous bone, as the gold standard, is difficult to meet clinical needs due to limited sources and secondary surgery, it has promoted the rapid development of artificial bone repair materials. Among the many orthopedic materials that have been on the market, traditional medical metals such as titanium and titanium alloys, stainless steel, etc. are widely used in the field of orthopedic implants due to their good mechanical properties. However, these materials still have some difficult to solve problems. For example, they will produce debris and release harmful metal ions due to corrosion and wear during their service in the human body, leading to the potential risk of inflammation and osteolysis. Secondary surgery is often required to remove them, which increases the risk and economic burden on patients. Therefore, it is necessary to develop degradable metal materials with excellent mechanical properties and good biocompatibility to replace traditional medical metals.

[0003] Current biodegradable metal materials mainly include magnesium-based, zinc-based and iron-based materials, among which magnesium-based materials are the most widely studied. However, magnesium and zinc-based materials have low mechanical strength and cannot be used to repair bone defects in load-bearing areas. Iron-based materials have good biocompatibility and excellent mechanical strength, and can effectively fix and support bone tissue in load-bearing areas. They have also gradually gained attention in recent years.

[0004] Although iron-based implants can effectively promote the regeneration and repair of bone tissue in load-bearing bone areas, their extremely low degradation rate causes a mismatch between the rate of new bone formation around the implant and the healing rate and degree of repair of bone defects. The conventional method is to add alloying elements inside the base material to accelerate degradation, but this method does not increase the degree of degradation of iron-based materials to meet their in vivo degradation requirements, and this method also has a great impact on the mechanical properties of the material. In addition, there are also methods that introduce pore structures into the iron matrix through template methods, placeholder filler methods, and 3D printing technology to increase the effective contact area with the corrosive environment to increase its degradation rate, but simply preparing porous iron cannot significantly increase the degradation rate. Summary of the invention

[0005] In view of the problems existing in the above process, the present invention intends to provide a surface-modified porous Fe-based scaffold with good mechanical properties and fast degradation rate.

[0006] The inventor's previous research (In vitro and 48 weeks in vivo performances of 3Dprinted porous Fe-30Mn biodegradable scaffolds (Acta Biomaterialia, 2021, 121, 724-740) showed that 3D printed Fe-based scaffolds showed good biocompatibility in the process of bone defect repair, but there was still a problem that the degradation rate of Fe-based materials was too slow, resulting in a mismatch between the material degradation rate and the new bone regeneration rate.

[0007] The inventor hopes to improve the degradation rate of the Fe-based scaffold by modifying the surface again on the existing porous structure. Chemical etching based on liquid phase solution immersion is often used for surface modification of porous scaffolds, but its etching speed is slow, and it is difficult to achieve uniform and controllable surface morphology of the scaffold. Dealloying is a common method for realizing nano-metal alloys (such as Mn-Cu, Mg-Al, etc.), but the nanoporous iron-based materials prepared directly by dealloying are not suitable as implant scaffolds, and so far, there has been no research report on the dealloying of Fe-Mn-based porous scaffolds. After research, the inventor found that by selecting different medium solutions, electrochemical dealloying can construct nano-topological structures of different morphologies on the surface of the Fe-based scaffold, increase its contact area with the solution, and then significantly improve its degradation rate without affecting the mechanical properties of the scaffold. In addition, the construction of the nano-topological structure on the surface of the scaffold can also promote the proliferation and differentiation of osteoblasts, enhance the osteogenic ability of the scaffold, and finally achieve the dynamic adaptation of the degradation rate and osteogenic regeneration rate of the Fe-based scaffold during service in vivo.

[0008] The technical solution adopted by the present invention is as follows:

[0009] A method for preparing a surface-modified porous iron-based scaffold, the specific process is as follows:

[0010] Using an electrochemical workstation, the porous iron-based scaffold was used as the working electrode, the Ag / AgCl electrode in 3.33 mol KCl solution was used as the reference electrode, and the platinum plate was used as the counter electrode. The surface-treated porous Fe-Mn scaffold was placed in an electrolyte solution and the open circuit potential and potentiodynamic polarization curves (time of 900 s, potentiodynamic polarization scan rate of 1 mVs -1 ) was measured to characterize the electrochemical properties of the Fe-based alloy, thereby determining the critical voltage. Constant potential dealloying treatment was performed at different times (20min-120min) and temperatures (25℃-45℃) within the critical voltage range (-0.85V, -0.2V).

[0011] Wherein, the electrolyte is an acidic sodium chloride solution or a dilute hydrochloric acid solution.

[0012] The type and concentration of the electrolyte used for dealloying, as well as the voltage, temperature, and time of dealloying will affect the surface morphology of the stent. Excessive dealloying will affect the stent structure, resulting in a decrease in mechanical properties. If the degree of dealloying is not enough, a suitable nanostructure cannot be formed and the degradation rate cannot be improved.

[0013] The porous iron-based stent can be prepared by common porous metal preparation methods, such as template method, placeholder filler method, 3D printing, organic sponge impregnation method, etc. Different porosities will affect the mechanical properties of the stent, so the stents prepared by different methods need to meet the basic mechanical properties requirements of in vivo implants. The porosity of the stent used in the embodiment of the present invention is about 70-80%.

[0014] Furthermore, in the acidic sodium chloride solution, Na:H=10:1-20:1, and the concentration of the dilute hydrochloric acid solution is 0.5%-5%.

[0015] Furthermore, in the acidic sodium chloride solution, Na:H=20:1; and the concentration of the dilute hydrochloric acid solution is 1.5%.

[0016] Furthermore, the porous Fe-based support is one of Fe-Mn alloy and Fe-Mn-Si alloy, and further is Fe-30Mn.

[0017] Fe-30Mn is a Fe-Mn alloy containing 30 wt % of Mn.

[0018] Fe-Mn alloys have better biocompatibility than other iron alloys, among which Fe-30Mn can maintain a good balance between the inhibitory effect on cell viability and mechanical properties.

[0019] Furthermore, when the electrolyte solution is a dilute hydrochloric acid solution, a constant potential dealloying treatment is performed at a constant voltage of -0.4V and a temperature of 25°C for 20 minutes. When the electrolyte solution is an acidic sodium chloride solution, a constant potential dealloying treatment is performed at a constant voltage of -0.65V and a temperature of 25°C for 30 minutes.

[0020] The invention also provides a surface microporous iron-based bracket using the method.

[0021] The present invention also provides application of the surface modified porous iron-based scaffold in bone repair materials.

[0022] Furthermore, the bone repair material is an auxiliary implant for repairing bone defects.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention performs dealloying treatment on the existing porous Fe-based scaffold, and constructs a suitable nanostructure within 100nm on the surface of the porous scaffold by screening the type of electrolyte and the voltage, temperature and time of dealloying, which will not affect its mechanical properties, and through the original micropores of the porous scaffold and the nanostructure, it can effectively increase its surface area and improve the degradation rate of the iron-based scaffold. It has been verified by experiments that it has good biocompatibility, can promote the proliferation and differentiation of osteoblasts on its surface, and thus achieve a perfect match between the degradation rate of the scaffold in vivo and the bone regeneration rate.

[0025] Instruction Manual

[0026] Figure 1 Scanning electron microscope (SEM) observation: a, d are untreated porous Fe-Mn scaffolds; b, e are HCl-treated porous Fe-Mn scaffolds; c, f are NaCl-treated porous Fe-Mn scaffolds

[0027] Figure 2 Scanning electron microscope (SEM) observation: a: HCl solution concentration 1.25%, b: HCl solution concentration 2.5%, c: HCl solution concentration 5%

[0028] Figure 3 Scanning electron microscope (SEM) observation: a: dealloying time 10min, b: dealloying time 20min, c: dealloying time 1h

[0029] Figure 4 Scanning electron microscope (SEM) observation: a: constant voltage -0.4V, b: constant voltage -0.3V, c: constant voltage -0.2V

[0030] Figure 5 Scanning electron microscope (SEM) observation: a: citric acid solution concentration 1.25%, b: citric acid solution concentration 2.5%, c: citric acid solution concentration 5%

[0031] Figure 6 Contact angle test on different material surfaces

[0032] Figure 7 Open circuit potential (a) and potentiodynamic polarization curves (b) of different scaffolds

[0033] Figure 8 Confocal laser scanning microscopy (CLSM) observation of MC3T3-E1 cultured on different material surfaces for 3 days

[0034] Fig. 9Cell proliferation analysis of MC3T3-E1 cells co-cultured with different materials for 1, 3, and 5 days

[0035] Fig.10 Cell proliferation test of different scaffold extracts

[0036] Fig.11 Expression results of osteogenesis-related genes after co-culture of MC3T3-E1 cells with different scaffold extracts

[0037] Fig.12 Comparison of mechanical strength of Fe-Mn scaffolds before and after dealloying DETAILED DESCRIPTION

[0038] The porous iron-based scaffold used in the embodiment of the present invention is prepared according to the method of the document In vitro and 48 weeks invivo performances of 3D printed porous Fe-30Mn biodegradable scaffolds (ActaBiomaterialia, 2021, 121, 724-740). The iron-based material used is Fe-30Mn.

[0039] Example 1

[0040] 1) Surface treatment of porous Fe-30Mn scaffold

[0041] The porous Fe-30Mn scaffold was cleaned with anhydrous ethanol, acetone and deionized water ultrasonically (temperature 25°C, ultrasonic power 120W, ultrasonic frequency 40KHz) for 15min in sequence, and then placed in a high-temperature drying oven at 60°C for 1h for subsequent surface modification.

[0042] 2) Surface modification of porous Fe-Mn / NaCl scaffolds

[0043] Weigh NaCl and HCl in a ratio (Na:H=20:1) and put them into a beaker. Add deionized water and stir for 10 minutes to prepare an acidic sodium chloride solution. Use an electrochemical workstation at room temperature (25°C) with the porous Fe-30Mn scaffold as the working electrode, the Ag / AgCl electrode in 3.33 mol KCl solution as the reference electrode, and the platinum plate as the counter electrode. The surface-treated porous Fe-Mn scaffold was placed in an acidic sodium chloride solution and the open circuit potential (900s) and potentiodynamic polarization curves (potentiodynamic polarization scan rate of 1mVs -1 ) was measured to characterize the electrochemical properties of Fe-Mn alloy. After the critical potential was obtained, a constant potential dealloying treatment was performed at a constant voltage of -0.65V and a temperature of 25°C for 30 minutes.

[0044] After the electrochemical reaction is finished, the sample is taken out, and the sample is lightly washed repeatedly with deionized water and ethanol until it is neutral, and then placed in a high-temperature drying oven at 60°C for 1 h to obtain Fe-Mn material (Fe-Mn / NaCl).

[0045] Example 2

[0046] 1) Surface treatment of porous Fe-30Mn scaffold

[0047] The porous Fe-30Mn scaffold was cleaned with anhydrous ethanol, acetone and deionized water ultrasonically (temperature 25°C, ultrasonic power 120W, ultrasonic frequency 40KHz) for 15min in sequence, and then placed in a high-temperature drying oven at 60°C for 1h for subsequent surface modification.

[0048] 2) Surface modification of porous Fe-Mn / HCl scaffolds

[0049] Dilute HCl with deionized water and stir for 10 minutes to prepare a 1.5% HCl solution. Use an electrochemical workstation at room temperature (25°C) with the porous Fe-30Mn scaffold as the working electrode, the Ag / AgCl electrode in 3.33M KCl solution as the reference electrode, and the platinum plate as the counter electrode. The surface-treated porous Fe-Mn scaffold was placed in a 1.5% HCl solution and the open circuit potential (900s) and potentiodynamic polarization curves (potentiodynamic polarization scan rate of 1mVs -1 ) was measured to characterize the electrochemical properties of Fe-Mn alloy. After the critical potential was obtained, a constant potential dealloying treatment was carried out at a constant voltage of -0.4V and a temperature of 25℃ for 20min.

[0050] After the electrochemical reaction is finished, the sample is taken out, and the sample is lightly washed repeatedly with deionized water and ethanol until it is neutral, and then placed in a high-temperature drying oven at 60°C for 1 h to obtain Fe-Mn material (Fe-Mn / HCl).

[0051] The scanning electron microscopy results of Examples 1 and 2 and the untreated porous iron-based scaffold are as follows: Figure 1 As shown, the contact angle test is as follows Figure 6 The compressive stress test results are shown in Fig.12 shown.

[0052] according to Figure 1 , 6 It can be seen that after the dealloying treatment, the morphology and micro-nanostructure of the porous Fe-based scaffold changed significantly, and the contact angle was smaller and the hydrophilicity was better. The hydrophilic surface is conducive to the adhesion and growth of cells. At the same time, Fig.12The test results of compressive stress show that the compressive stress of the iron-based stent surface modified by the present invention decreases less, that is, the method of the present invention can maintain good mechanical properties while increasing the degradation rate, meeting the requirements of stent implantation in vivo.

[0053] Comparison of different dealloying conditions in the examples

[0054] 1. Medium solutions of different concentrations

[0055] 1) Surface treatment of porous Fe-30Mn scaffold

[0056] The porous Fe-30Mn scaffold was cleaned with anhydrous ethanol, acetone and deionized water ultrasonically (temperature 25°C, ultrasonic power 120W, ultrasonic frequency 40KHz) for 15min in sequence, and then placed in a high-temperature drying oven at 60°C for 1h for subsequent surface modification.

[0057] 2) Surface modification of porous Fe-Mn / HCl scaffolds

[0058] HCl was diluted with deionized water and stirred for 10 minutes to prepare HCl solutions with concentrations of 1.25%, 2.5%, and 5%. An electrochemical workstation was used at room temperature (25°C), with the porous Fe-30Mn scaffold as the working electrode, the Ag / AgCl electrode in 3.33 mol KCl solution as the reference electrode, and the platinum plate as the counter electrode. The surface-treated porous Fe-Mn scaffolds were placed in HCl solutions of different concentrations, and the open circuit potential (900 s) and potentiodynamic polarization curves (potentiodynamic polarization scan rate of 1 mVs -1 ) was measured to characterize the electrochemical properties of Fe-Mn alloy. After the critical potential was obtained, a constant voltage of -0.4V and a temperature of 25℃ were selected to carry out a constant potential dealloying treatment for 20 minutes.

[0059] After the electrochemical reaction is over, take out the sample, wash it with deionized water and ethanol repeatedly until it is neutral, and then put it in a high-temperature drying oven at 60°C for 1 hour to obtain Fe-Mn materials treated with HCl medium solutions of different concentrations. The scanning electron microscopy results are shown in the figure. Figure 2 shown.

[0060] 2. Different dealloying time

[0061] 1) Surface treatment of porous Fe-30Mn scaffold

[0062] The porous Fe-30Mn scaffold was cleaned with anhydrous ethanol, acetone and deionized water ultrasonically (temperature 25°C, ultrasonic power 120W, ultrasonic frequency 40KHz) for 15min in sequence, and then placed in a high-temperature drying oven at 60°C for 1h for subsequent surface modification.

[0063] 2) Surface modification of porous Fe-Mn / HCl scaffolds

[0064] Dilute HCl with deionized water and stir for 10 minutes to prepare three sets of 1.25% HCl solutions. Use an electrochemical workstation at room temperature (25°C), with the porous Fe-30Mn scaffold as the working electrode, the Ag / AgCl electrode in 3.33 mol KCl solution as the reference electrode, and the platinum plate as the counter electrode. The surface-treated porous Fe-Mn scaffolds were placed in HCl solutions of different concentrations, and the open circuit potential (900s) and potentiodynamic polarization curves (potentiodynamic polarization scan rate of 1mVs -1 ) was measured to characterize the electrochemical properties of Fe-Mn alloy. After the critical potential was obtained, a constant voltage of -0.4V and a temperature of 25℃ were selected to perform constant potential dealloying treatment for 10min, 20min, and 1h respectively.

[0065] After the electrochemical reaction is over, take out the sample, wash it with deionized water and ethanol repeatedly until it is neutral, and then put it in a high-temperature drying oven at 60℃ for 1h to obtain Fe-Mn(HCl) materials with different treatment times. The scanning electron microscopy results are as follows: Figure 3 shown.

[0066] 3. Different dealloying current

[0067] 1) Surface treatment of porous Fe-30Mn scaffold

[0068] The porous Fe-30Mn scaffold was cleaned with anhydrous ethanol, acetone and deionized water ultrasonically (temperature 25°C, ultrasonic power 120W, ultrasonic frequency 40KHz) for 15min in sequence, and then placed in a high-temperature drying oven at 60°C for 1h for subsequent surface modification.

[0069] 2) Surface modification of porous Fe-Mn / HCl scaffolds

[0070] Dilute HCl with deionized water and stir for 10 minutes to prepare three sets of 1.25% HCl solutions. Use an electrochemical workstation at room temperature (25°C), with the porous Fe-30Mn scaffold as the working electrode, the Ag / AgCl electrode in 3.33 mol KCl solution as the reference electrode, and the platinum plate as the counter electrode. The surface-treated porous Fe-Mn scaffolds were placed in HCl solutions of different concentrations, and the open circuit potential (900s) and potentiodynamic polarization curves (potentiodynamic polarization scan rate of 1mVs -1 ) was measured to characterize the electrochemical properties of Fe-Mn alloy. After obtaining the critical potential, constant voltages of -0.4V, -0.3V, and -0.2V were selected and the temperature was 25℃ for 20min of constant potential dealloying treatment.

[0071] After the electrochemical reaction is over, take out the sample, wash it repeatedly with deionized water and ethanol until it is neutral, and then dry it in a high-temperature drying oven at 60°C for 1 hour to obtain Fe-Mn (HCl) materials treated with different dealloying currents. The scanning electron microscopy results are shown in Figure 2. Figure 4 shown.

[0072] 4. Different types of medium solutions

[0073] 1) Surface treatment of porous Fe-30Mn scaffold

[0074] The porous Fe-30Mn scaffold was cleaned with anhydrous ethanol, acetone and deionized water ultrasonically (temperature 25°C, ultrasonic power 120W, ultrasonic frequency 40KHz) for 15min in sequence, and then placed in a high-temperature drying oven at 60°C for 1h for subsequent surface modification.

[0075] 2) Surface modification of porous Fe-Mn / citric acid scaffolds

[0076] Dilute citric acid with deionized water and stir thoroughly for 10 minutes to prepare 1.25%, 2.5%, and 5% citric acid solutions. Use an electrochemical workstation at room temperature (25°C), with the porous Fe-30Mn scaffold as the working electrode, the Ag / AgCl electrode in 3.33 mol KCl solution as the reference electrode, and the platinum plate as the counter electrode. The surface-treated porous Fe-Mn scaffold was placed in a 1.5% citric acid solution, and the open circuit potential (900s) and potentiodynamic polarization curves (potentiodynamic polarization scan rate of 1mVs -1 ) was measured to characterize the electrochemical properties of Fe-Mn alloy. After the critical potential was obtained, a constant potential dealloying treatment was performed at a voltage of -0.6V and a temperature of 25℃ for 1h.

[0077] After the electrochemical reaction is over, take out the sample, wash it repeatedly with deionized water and ethanol until it is neutral, and then dry it in a high-temperature drying oven at 60°C for 1 hour to obtain Fe-Mn material (Fe-Mn / citric acid). The scanning electron microscopy results are as follows: Figure 5 shown.

[0078] according to Figure 2 , 3 4 It can be seen that the dealloying effects are significantly different when the dielectric solution concentration, dealloying time, and dealloying current intensity are different. When the HCl dielectric solution concentration is greater than 5%, the dealloying time is 10 min and 1 h, and the dealloying voltage is -0.3 V and -0.2 V, the structural distribution on the surface of the obtained stent is irregular, and no uniform nanostructure is formed. Therefore, only by selecting appropriate dielectric solution concentration, dealloying time, and voltage can a uniformly distributed lamellar nanostructure be formed on the stent surface.

[0079] from Figure 5 and Figure 2 By comparison, it can be seen that when citric acid is selected as the medium solution, although dealloying can be achieved, no matter how its concentration is adjusted, a uniformly distributed lamellar nanostructure cannot be formed. Therefore, only by selecting a suitable medium solution can a suitable nanostructure be formed.

[0080] Example Degradation Rate Determination

[0081] Material setting: Control group: untreated porous Fe-Mn scaffold group; Experimental group: Fe-Mn scaffold group (Fe-Mn / NaCl) after dealloying treatment in Example 1, Fe-Mn scaffold group (Fe-Mn / HCl) after dealloying treatment in Example 2

[0082] The corrosion resistance of the stent was tested electrochemically to evaluate the degradation rate of the material. Figure 7 As shown, the corrosion potential of the Fe-Mn / NaCl and Fe-Mn / HCl stents is significantly lower than that of the control pure Fe-Mn stent, indicating that the stent after dealloying treatment has lower electrochemical stability and higher corrosion tendency, and is more easily degraded in the human body.

[0083] Example Observation of cell morphology and proliferation experiments on different scaffold surfaces

[0084] Material setting: Control group: blank control without scaffold; Experimental group: untreated porous Fe-Mn scaffold group, Fe-Mn scaffold group treated with dealloying in Example 1 (Fe-Mn / NaCl)

[0085] Cells used: Mouse embryonic osteoblast precursor cells (MC3T3-E1)

[0086] Culture method: indirect culture, cell density: 2×10 4 / well plate

[0087] Observation method: Cell morphology observation was performed by staining the cells on the surface of the material using the FDA / PI dual-color fluorescence method and then observing them through laser confocal microscopy; cell proliferation experiments were tested using the CCK-8 method.

[0088] from Figure 8 The staining results show that MC3T3-E1 grows well on all material surfaces and presents normal cell morphology. As the culture time increases, the cell density of MC3T3-E1 inoculated on the surfaces of the three groups of materials gradually increases, indicating that the dealloyed Fe-Mn material has excellent cell compatibility.

[0089] Fig. 9The results of CCK-8 observation showed that during the whole co-culture period, the cells in both groups showed a proliferation trend, indicating that the cell growth activity was good. However, compared with the blank control, the proliferation was less than that of the control group. This may be because the Fe-Mn scaffold degraded and produced Fe 2+ , Mn 2+ , and the local ion concentration is high, which affects the cells.

[0090] Example Test of cell proliferation and osteogenic gene expression effects of different scaffold extracts

[0091] Material setting: Control group: blank control; Experimental group: Fe-Mn scaffold group (Fe-Mn / NaCl) treated with dealloying in Example 1, Fe-Mn scaffold group (Fe-Mn / HCl) treated with dealloying in Example 2

[0092] Cells used: Mouse embryonic osteoblast precursor cells (MC3T3-E1)

[0093] After the scaffold extract was prepared according to the GB / T16886 medical device biological evaluation series standard, it was co-cultured with MC3T3-E1 cells.

[0094] like Fig.10 As shown, although the scaffolds in the HCl group and the NaCl group have different degradation rates, after the 5th day of culture, the cell proliferation density of the extracts of the two groups of materials has no significant difference from that of the blank group, indicating that the surface-modified porous iron-based scaffold prepared by the present invention has good biocompatibility.

[0095] like Fig.11 As shown in the figure, from the expression results of osteoblast-related genes after co-culture of different scaffold extracts with MC3T3-E1 cells, it can be seen that after regulating the micro-nano morphology and structure of the scaffold surface through dealloying treatment, the proliferation and differentiation of osteoblasts on its surface can be promoted.

Claims

1. A method for preparing a surface-modified porous iron-based scaffold, characterized in that: The method comprises the following steps: performing a constant potential dealloying treatment on the porous iron-based support for 20 minutes to 120 minutes at 25°C to 45°C and a critical voltage in the range of -0.85V to -0.2V; wherein the electrolyte is an acidic sodium chloride solution or a dilute hydrochloric acid solution; The acidic sodium chloride solution contains Na + :H + =10:1-20:1, the mass concentration of the dilute hydrochloric acid solution is 0.5%-5%.

2. The preparation method according to claim 1, characterized in that: The acidic sodium chloride solution contains Na + :H + =20:1; the mass concentration of the dilute hydrochloric acid solution is 1.5%.

3. The preparation method according to claim 1, characterized in that: The porous Fe-based support is any one of Fe-Mn alloy and Fe-Mn-Si alloy.

4. The preparation method according to claim 3, characterized in that: The porous Fe-based support is Fe-30Mn.

5. The preparation method according to claim 1, characterized in that: When the electrolyte solution is a dilute hydrochloric acid solution, a constant potential dealloying treatment is performed at a constant voltage of -0.4 V and a temperature of 25° C. for 20 minutes.

6. The preparation method according to claim 1, characterized in that: When the electrolyte solution is an acidic sodium chloride solution, a constant potential dealloying treatment is performed for 30 minutes at a constant voltage of -0.65 V and a temperature of 25°C.

7. A surface-modified porous iron-based scaffold, characterized in that: The method is prepared by any one of claims 1 to 6.

8. The surface-modified porous iron-based scaffold according to claim 7, characterized in that: The surface-modified porous iron-based scaffold is used for preparing auxiliary implants for repairing bone defects.